Cover Image, Volume 27, Issue 10. Issue 10 (5th October 2018) - Dunne, Simon; Coffey, Laura; Sharp, Linda; Timmons, Aileen; Desmond, Deirdre; Gooberman‐Hill, Rachael; O'Sullivan, Eleanor; Keogh, Ivan; Timon, Conrad; Gallagher, Pamela
Abstract : The cover image, by Simon Dunne et al., is based on the Paper Barriers to active self‐management following treatment for head and neck cancer: Survivors' perspectives, https://doi.org/10.1002/pon.4835 .